FREEMIUM MULTI-SIDED PLATFORM BUSINESS MODEL: MOSQUE KITCHEN AS A SOURCE OF FREE FOOD, EMPLOYMENT AND EMPOWERMENT OF B40S FOOD-PRENEURS - Ahmad Dahlan, Abdul Rahman; Jamaludin Ibrahim (Journal of Information Systems and Digital Technologies, 2021)
COVID-19 crisis has pushed more low-income or poor B40 urban Malaysian families into poverty, based on the“Families on The Edge” UNICEF report dated October 2020. The poverty rate of these B40 urban families in 2020 is higher than 2019, with 50% of the families living in absolute poverty. 70% of these households had affected their ability to meet their basic living expenses. 37% said that they are struggling to purchase enough food for their families, while 35% are unable to pay their bills on time. This paper adapted the Design Thinking (DT) methodology. DT includes conducting literature review, benchmarking, and interviews to understand and define the key B40s problems; ideation of possible solution options, validation of solution options by various customer segments; and to suggest a conceptual freemium multi-sided platform business model as a possible solution. An initial business model using Business Model Canvas (BMC) framework was formulated; tested and validated by various customer segments. Hence, the main contribution of this paper is to offer a validated conceptual business model in transforming current mosque kitchen (or mKitchen) as a potential in (a) providing job employment while reskilling, empowering, and nurturing the B40s as food entrepreneurs, (b) providing free food for the needy B40s communityby the B40s food-preneurs, and (c) generating income for the masjid via rental of kitchen facilities. This is to turn the B40 community from Zakat receivers to Zakat contributors. The conceptual mKitchen freemium multi-sided platform business model with platform network effects can be customised for implementation by mosques and community centres.